Deprivasi Budaya pada Remaja Kalangan Marginal - Nurhidayati, Euis (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2017)
This study aims to: 1) describe the characteristics of deprivation of culture in the students of secondary school (SMP), which is in an environment characterized by cultural deprivation. 2) Know the difference in strength characteristics of cultural deprivation boys and girls, as well as the differences between classes. Participants of this study lived in the school environment and farm workers Banten, they are Mitra Persada junior high school students of class VII, VIII and IX amounting to 90 people and consists of 37 boys and 40 girls. Measuring instrument used is an instrument consisting of 30 items and has been tested for validity and reliability, the instrument was made based on the indicators of three (3) main aspects of deprivation of culture, namely: 1) Development Property, 2) Language, 3) Attitude. And measurement using a questionnaire using the Likert scale. From there Descriptive Test standard deviation is very large (more than 30% of the mean) showed a large variation or the existence of a considerable gap from the lowest score and the highest score. Based on the calculations above descriptive, known from the mean total score of social deprivation in the can that is 79.12 which is 64.85% of the total score of each item that is ideal 122. It can be concluded that the impact of deprivation Mitra Persada junior high school students is still relatively high. While the Mann-Whitney test concluded that there are significant differences in the characteristics of cultural deprivation boys and girls. And grade level provides a significant effect on cultural deprivation.